2021
DOI: 10.1371/journal.pone.0261784
|View full text |Cite
|
Sign up to set email alerts
|

Amount and type of physical activity and sports from one year forward after hip or knee arthroplasty—A systematic review

Abstract: Introduction After rehabilitation following total hip or knee arthroplasty (THA/TKA), patients are advised to participate in physical activity (PA) and sports. However, profound insight into whether people adopt a physically active lifestyle is lacking. Aim is to gain insight into the performed amount and type of PA (including sports) and time spent sedentarily by persons after THA/TKA. Methods A systematic review (PROSPERO: CRD42020178556). Pubmed, Cinahl, EMBASE and PsycInfo were systematically searched fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 149 publications
(329 reference statements)
0
3
1
Order By: Relevance
“…Our study reports higher levels of leisure-time physical activity in the THA group than previously described [7]. This may be explained by selection.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Our study reports higher levels of leisure-time physical activity in the THA group than previously described [7]. This may be explained by selection.…”
Section: Discussioncontrasting
confidence: 54%
“…After THA, patients are more likely to return to low-intensity activities such as walking and cycling than high-intensity activities such as running and tennis [6]. Physical activity levels in the years following THA seem to be low, with less than half of subjects meeting health-enhancing guidelines [7]. Few studies report on long-term levels of physical activity after THA compared with a control population [8].…”
mentioning
confidence: 99%
“…Authors have reported that the majority of patients with OA do not meet guideline recommendations for daily activity [5,6], performing less PA than age-matched subjects without OA [7]. In addition, several reports have suggested that these patients spend the majority of their time in sedentary behaviors [8][9][10], which has been shown to significantly impact the risk of morbidity and mortality in adult populations [11].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Postoperative dissatisfaction is often attributed to patients' unmet expectations, particularly regarding their desire to engage in low-impact exercise and maintain participation in intermediate-to high-impact activities. [9][10][11] In response to patients' heightened expectations of physical activity after TKA, there is a growing need to determine the appropriate level of physical activity and acceptable types of activities for these patients. 12,13 Traditional physicianprovided outcomes alone may not sufficiently address these questions, highlighting the importance of incorporating patient-reported outcome measures (PROMs).…”
Section: Introductionmentioning
confidence: 99%